2018
DOI: 10.1002/cctc.201801581
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus‐doped Isotype g‐C3N4/g‐C3N4: An Efficient Charge Transfer System for Photoelectrochemical Water Oxidation

Abstract: Constructing isotype g‐C3N4/g‐C3N4 heterojunction is an approach to improve the efficiency of g‐C3N4 towards solar‐assisted oxidation of water. Such functional configuration can effectively overcome the intrinsic drawback of rapid charge recombination of g‐C3N4. Here, a modified g‐C3N4, with homogeneous phosphorus doping, is prepared in this work through a phosphide‐involved gas phase reaction. The resulting P‐g‐C3N4 displays altered electronic structure, including upshifted band edge potential, narrowed band … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…Previous reports have confirmed that the electron‐withdrawing group (HO−C=O) is favorable for promoting charge separation during photocatalysis . The high resolution N 1s XPS spectra of 3D C/g‐C 3 N 4 ‐3 can be decomposed into three different peaks centered at 398.8, 400.1, and 401.3 eV (Figure d), which are regarded as the sp 2 ‐bonded N(C−N=C), tertiary nitrogen N‐(C) 3 , and C‐NH, respectively, in accordance with those of bulk g‐C 3 N 4 .…”
Section: Resultssupporting
confidence: 67%
“…Previous reports have confirmed that the electron‐withdrawing group (HO−C=O) is favorable for promoting charge separation during photocatalysis . The high resolution N 1s XPS spectra of 3D C/g‐C 3 N 4 ‐3 can be decomposed into three different peaks centered at 398.8, 400.1, and 401.3 eV (Figure d), which are regarded as the sp 2 ‐bonded N(C−N=C), tertiary nitrogen N‐(C) 3 , and C‐NH, respectively, in accordance with those of bulk g‐C 3 N 4 .…”
Section: Resultssupporting
confidence: 67%
“…[39] Yu's work showed that homophase junction provided smoother channel for charge transfer. [39] Moreover, Wang, [40] Dong, [41] et al, [42][43][44] carried out researches about g-C 3 N 4 /g-C 3 N 4 heterojunction. As the defects in the catalyst become the center of charge recombination, the photocatalytic performance of g-C 3 N 4 based isotype heterojunction or homophase junction is not satisfactory.…”
Section: Introductionmentioning
confidence: 99%
“…5 Cu-based materials have shown great performance in comparison with other cited system, however, it suffers with serious problem of chemical stability due to the photocorrosion process, shortening its lifetime as PEC component. To boost the PEC cell performance using photocatalysts, several strategies have been pursued, for instance, extending the absorption spectra towards infrared, improve charge carrier kinetics and increase the active sites at the surface including the doping with anions or cations, [6][7][8] surface coupling with metals or semiconductors 9,10 and lm morphology design (nanoscaling).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to graphite and carbon nanotubes, graphene exhibits much greater surface area and exceptional conductivity making it a potential candidate for different uses. Graphene has been reported in several applications such as a biosensors, 38 gas sensors, 8 electronic device design, 39 transistors, fuel cells, 40 photovoltaic devices, 41 photocatalytic hydrogen generation, etc.…”
Section: Introductionmentioning
confidence: 99%